A Social Work Model of Historical Trauma. (16th June 2022) - Rosenwald, Mitchell; Baird, Jennifer; Williams, Jennifer
Abstract: This article introduces a Social Work Model of Historical Trauma . The model draws from social work perspectives (ecosystems theory and the life model, human rights philosophy, race-based traumatic stress injury theory and attachment theory), disparities research, social work issues and policy statements, social work ethics and epigenetics. Assessment and intervention in micro, mezzo and macro domains are discussed. The article concludes with a case vignette and model application. Abstract : This article provides social workers with a framework to help clients who have been impacted by 'historical trauma' such as racism, sexism and homophobia. This framework provides tools for understanding the impact of historical trauma. Using this knowledge, social workers can more skilfully assess and intervene with their clients who have been affected by historical trauma. These skills allow social workers to help clients in direct practice as well as at the agency and community level.